PENGARUH LIMBAH KARET TERHADAP VIABILITAS TELUR BIBIT IKAN MAS (Cyprinus carpio L.) - Sumarmin, Ramadhan (IAIN Batusangkar, 2012)
One of the pollutants that get into the water of the river in Padang city comes from waste rubber factory. The river water is still used for various purposes by the people including seeding and caring goldfish with uncertain products. Based on this situation, the research was done in order to find out the effect of the rubber waste on the viability and the seedling growth rate of goldfish. The research used completely randomized design with 5 and 10 treatments. The observation on the hatching eggs after 2 days of incubation at various treatment and measuring the body weight and length of the fish was done 5 times within five days. The data were analyzed by using ANOVA p <0.05 and BJND extended test. As the results it was found the highest average of viability was in treatment A (control) 76.7% and the lowest at treatment E 30%. Whereas there is no seed growth rate difference between treatments A (control) and B (5%), but significantly different p <0.05 with treatment C, D, and E. It can be concluded that the higher the concentration of waste rubber factory the lower goldfish viability. The concentration of factory waste up to 5% is not influential against the growth seedling goldfish. Key words: waste rubber, viability, gold fish egg